Cape Verde : 2001 Article IV Consultation-Staff Report and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2001)
In the conclusion of the previous Article IV Consultation, Executive Directors welcomed the elimination of quantitative import restrictions and the liberalization of foreign exchange regulations, and Directors emphasized the need to consolidate the progress made in containing the fiscal imbalances by continuing with prudent expenditure policies and further strengthening the tax system and budgetary procedures. Fiscal slippages occurred in the second half of 1999 and led to pressures on the balance of payments. Structural reforms created an environment conducive to private sector activity.